Ginsenoside Rb1 ameliorates CKD‐associated vascular calcification by inhibiting the Wnt/β‐catenin pathway. Issue 10 (19th August 2019) - Zhou, Peng; Zhang, Xinyu; Guo, Mengqi; Guo, Rong; Wang, Lei; Zhang, Zihao; Lin, Zongwei; Dong, Mei; Dai, Hongyan; Ji, Xiaoping; Lu, Huixia
Abstract: Vascular calcification (VC) is a pathological process underpinning major cardiovascular conditions and has attracted public attention due to its high morbidity and mortality. Chronic kidney disease (CKD) is a common disease related to VC. Ginsenoside Rb1 (Rb1) has been reported to protect the cardiovascular system against vascular diseases, yet its role in VC and the underlying mechanisms remain unclear. In this study, we established a CKD‐associated VC rat model and a β‐glycerophosphate (β‐GP)‐induced vascular smooth muscle cell (VSMC) calcification model to investigate the effects of Rb1 on VC. Our results demonstrated that Rb1 ameliorated calcium deposition and VSMC osteogenic transdifferentiation both in vivo and in vitro. Rb1 treatment inhibited the Wnt/β‐catenin pathway by activating peroxisome proliferator‐activated receptor‐γ (PPAR‐γ), and confocal microscopy was used to show that Rb1 inhibited β‐catenin nuclear translocation in VSMCs. Furthermore, SKL2001, an agonist of the Wnt/β‐catenin pathway, compromised the vascular protective effect of Rb1. GW9662, a PPAR‐γ antagonist, reversed Rb1's inhibitory effect on β‐catenin. These results indicate that Rb1 exerted anticalcific properties through PPAR‐γ/Wnt/β‐catenin axis, which provides new insights into the potential theraputics of VC.